2014
DOI: 10.1136/bmjopen-2013-004259
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose prednisolone treatment of early rheumatoid arthritis and late cardiovascular outcome and survival: 10-year follow-up of a 2-year randomised trial

Abstract: ObjectiveTo examine the long-term effects of early low-dose prednisolone use in patients with rheumatoid arthritis (RA) on cardiovascular (CV) morbidity and mortality.DesignRetrieval of data from a 2-year open randomised trial comparing prednisolone 7.5 mg/day in addition to disease-modifying antirheumatic drugs (DMARDs) with DMARD therapy alone. Participants were followed for 10 years since inclusion into the original prednisolone trial or until occurrence of the studied outcomes.SettingSecondary level of car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 42 publications
2
32
0
7
Order By: Relevance
“…Most notably, two recent studies suggested a dose-dependent increase in mortality in RA27 28; del Rincón et al 27 revealed a daily threshold dose of 8 mg at which all-cause mortality increased with GC dose (adjusted HR=1.78; 95% CI 1.22 to 2.60), and in the German register Rheumatoid Arthritis oBservation of BIologic Therapy (RABBIT), use of GC >5 mg/day was associated with increased mortality risk, independent of RA activity 28. Moreover, a 10-year follow-up study examined cardiovascular events and deaths in early patients with RA with no history of CVD who were included in a recent open-label randomised trial of low-dose prednisolone (7.5 mg/day) over the first 2 years of early RA Better Anti-Rheumatic PharmacOTherapy (BARFOT+): low-dose prednisolone use was associated with increased incidence of cerebrovascular events and, although not significant, increased mortality 29. Long-term follow-up of Computer Assisted Management in Early Rheumatoid Arthritis (CAMERA II) patients with early RA who received prednisone at 10 mg/day for at least 2 years revealed increased cardiovascular risk and, although not significant, increased mortality 30…”
Section: Discussionmentioning
confidence: 99%
“…Most notably, two recent studies suggested a dose-dependent increase in mortality in RA27 28; del Rincón et al 27 revealed a daily threshold dose of 8 mg at which all-cause mortality increased with GC dose (adjusted HR=1.78; 95% CI 1.22 to 2.60), and in the German register Rheumatoid Arthritis oBservation of BIologic Therapy (RABBIT), use of GC >5 mg/day was associated with increased mortality risk, independent of RA activity 28. Moreover, a 10-year follow-up study examined cardiovascular events and deaths in early patients with RA with no history of CVD who were included in a recent open-label randomised trial of low-dose prednisolone (7.5 mg/day) over the first 2 years of early RA Better Anti-Rheumatic PharmacOTherapy (BARFOT+): low-dose prednisolone use was associated with increased incidence of cerebrovascular events and, although not significant, increased mortality 29. Long-term follow-up of Computer Assisted Management in Early Rheumatoid Arthritis (CAMERA II) patients with early RA who received prednisone at 10 mg/day for at least 2 years revealed increased cardiovascular risk and, although not significant, increased mortality 30…”
Section: Discussionmentioning
confidence: 99%
“…Доказан дозозависимый эффект ГК на повыше-ние вероятности развития ССО в группе больных с воспа-лительными артритами [36,108,109]. Длительное приме-нение ГК приводит к увеличению риска смертности.…”
Section: рекомендация 6 скрининг бессимптомных атб с ис-пользованиемunclassified
“…Обращается особое внимание на риск НР (инфекционных осложнений и кардиоваску-лярной патологии, увеличения массы тела, артериальной гипертензии, диабета, катаракты, остеопороза), который нарастает при достижении высокой кумулятивной дозы ГК и их длительном приеме [83][84][85][86][87][88][89][90][91].…”
Section: таблицаunclassified